OPTIMALISASI PENDIDIKAN AGAMA ISLAM (PAI) DI SEKOLAH - Dwi Permana, Mirza; Wardan, Khusnul (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2024)
The optimization of Islamic Religious Education (PAI) in Indonesian schools faces complex challenges, such as curriculum changes, increasingly plural social dynamics, and the need to adapt to technological advancements. This study aims to explore approaches to enhance the effectiveness of PAI through a literature review method, encompassing the analysis of theories, concepts, and relevant teaching strategies. The findings identify several key approaches, including humanistic and contextual approaches, as well as the utilization of digital technology as solutions to strengthen PAI learning. The main recommendations include adjusting teaching materials to be more contextual, improving teacher capacity through continuous training, and integrating technology to create innovative and interactive learning experiences. These findings are expected not only to enrich the theory of Islamic Education Philosophy but also to provide practical contributions to improving the quality of PAI teaching in Indonesian schools, making it more relevant, inclusive, and effective.